Investigating Consumer Perceived Value and Intentions toward Green Luxury Hotels - Sampaio Costa (Curtin University, 2023)
Can luxury and sustainability coexist? The luxury symbolic nature of irrationality, excess and inequality has been argued to conflict with the intrinsic nature of sustainable development, which represents equalitarian and humanitarian values. Further, intuitively the need to sacrifice some luxuries for the sake of sustainability could elicit lower perceived value. The current study aimed at testing this paradoxical relationship by applying the perceived value framework to the context of luxury hotels. Using an experimental design, it examined differences in perceived functional, symbolic, social, financial, altruistic and hedonic value and intention to stay at a generic luxury versus green luxury hotels. It also examined the differences in perceptions for sacrifice versus non-sacrifice green luxury hotel scenarios. Environmental consciousness and consumer values were also examined for their effects on the customer. The quantitative survey was conducted in Australia with 800 luxury hotel guests and data was analysed using t-tests, ANCOVAs, multiple regression analyses as well as cluster analysis. The results revealed an enhanced perceived value and intentions for green luxury hotels, with an encouraging dominance of the sacrifice conditions, lending support to the binomial identity values theory as well as challenging the loss aversion theory. It offers a range of insights for hotel managers and marketers to develop impactful marketing communication, products and targeted advertising for specific consumer segments. The current study also differentiates from previous studies as it adopts an objective experimental comparison to identify the specific effects of green initiatives on luxury hotel perceptions.